Tanjung Priok Police Community Policing in the Security of Mbah Priok - Ramona Gusti, Wan Deni; Setyabudi, Chairul Muriman; Sutrisno, Sutrisno (Fakultas Syariah INSURI Ponorogo, 2023)
Haul Mbah Priok's activities have the potential to cause disturbances in Kamtibmas, especially during the Covid-19 pandemic. Police are expected to play an active role in preventing various forms of social problems, including problems that may arise at Haul Mbah Priok. This study aims to determine the relationship between the National Police and the Community in Securing Haul Mbah Priok during the Covid-19 pandemic by the Tanjung Priok Port Police. This research was conducted with a qualitative approach. Sources of data in this study include the Head of Tanjung Priok Port Police, Head of Binmas, Head of Criminal Investigation Unit, Head of Intelligence and Security, Tomas and Toga, and the community. The methodology uses a qualitative approach. The results showed that the haul Mbah Priok vulnerability potential was very high. The results of this study are to equate perceptions of the technical plan for securing the Mbah Priok haul. Police-community relations in securing Haul Mbah Priok are no longer based on the legality of the Tanjung Priok Port Police's actions, but community recognition of the security measures carried out by the police which require